SATELLITE DETECTION OF WILDLAND FIRES IN SOUTH AMERICA - White, Benjamin Leonardo Alves (Floresta, 2019)
The detection of wildland fires by satellites began in the 1980s. Since them, satellite images have been used as an early wildfire detection system, for estimate burnt area and for assist the development of strategies focused on wildfires prevention. This study aims to analyse, spatially and temporally, the hot spots detected by the AQUA satellite (MODIS sensor), processed by the INPE using the “Collection 5” detection algorithm, in all South America for the years 2003 to 2017. A total of 4,953,769 hot spots where analysed and Brazil had the highest hot spot incidence while Paraguay presented the highest hot spots occurrence per area (density). The year of 2004 had the highest number of hot spots detected, while 2013 the lowest. Significant linear trend was observed only in two countries: Peru and Chile, in both cases indicating an uptrend during the assessed period. The month with the highest fire activity in South America was September, the least May. Each country presented differences regarding the months with higher and lower hot spots detected, mainly due to different rainfall patterns. The annual changes in the wildland fire occurrence observed in this study are mostly due to human behaviour linked with climate variations caused by the El Niño and La Niña.